Hybrid Test on a Simply Supported Bridge With High-Damping Rubber Bearings - Yang, Chengyu; Cai, Xuesong; Lai, Ziqin; Yuan, Yong (Frontiers in Built Environment, 2020)
In this study, hybrid simulation techniques are used to test earthquake excitation on a supported bridge with High-damping rubber (HDR) bearings, which are widely used in girder bridges. It is impractical to make a full-scale or large-scale test of a whole bridge in the laboratory and substructure hybrid simulation techniques can overcome these scale issues to some extent. Using the software framework OpenFresco, the study involved a continuous exchange of data between a numerical model and a physical specimen. An experimental bearing element is introduced to the HDR bearings, and the remainder of the structure is modeled with beam-column elements for numerical analysis. These hybrid simulation results match the analytical results under the designated earthquake excitation. Therefore, this technique reproduces the seismic performance of a simply supported bridge with HDR bearings. This series of dynamic hybrid simulations of a simply supported bridge provides useful insights into the selection of HDR bearings. The study analyses and discusses the mechanical properties of these HDR bearings when subject to earthquake excitations.